Portrait of Moderate Islam Within Muslim University Students in Indonesia - Ahmad Jais; Sumin Sumin (Al-Albab)
The violence in the name of religion is now not only happening in the Middle East but has also penetrated Indonesia. Indonesia is not only known as a Muslim-majority country that is friendly and peace-loving but also has a diversity of religions, ethnicities, races, and cultures that have the potential to trigger conflict at any time. Violations of religious freedom in Indonesia have increased dramatically in recent years. This study is aimed to explore the understanding of Muslim students in Indonesia about Islamic moderation, the perceptions of Muslim students in Indonesia about the application of Islamic moderation, and the challenges and strategies of universities in implementing Islamic moderation on Muslim students in Indonesia. This study uses phenomenology approach with Muslim students as the object of the research. The participants were selected purposively as many as 20 students. This study finds that Muslim students in Indonesia characterize Islamic moderation as Muslims who are open to technological change, tolerant and harmonious with other Muslims and non-Muslims, non-violent, democratic, and access to comprehensive Islamic sources. Even though Muslim students in Indonesia have implemented Islamic moderation, there are still misconceptions about Islamic moderation. The challenge of implementing Islamic moderation in Muslim students is that they are easily exposed to extreme understanding through social media or the pragmatic and rational Islamic community.